Efficient CRISPR-Mediated Post-Transcriptional Gene Silencing in a Hyperthermophilic Archaeon Using Multiplexed crRNA Expression. Issue 10 (1st October 2016) - Zebec, Ziga; Zink, Isabelle Anna; Kerou, Melina; Schleper, Christa
Abstract: CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats)-mediated RNA degradation is catalyzed by a type III system in the hyperthermophilic archaeon Sulfolobus solfataricus . Earlier work demonstrated that the system can be engineered to target specifically mRNA of an endogenous host reporter gene, namely the β-galactosidase in S. solfataricus . Here, we investigated the effect of single and multiple spacers targeting the mRNA of a second reporter gene, α-amylase, at the same, and at different, locations respectively, using a minimal CRISPR (miniCR) locus supplied on a viral shuttle vector. The use of increasing numbers of spacers reduced mRNA levels at progressively higher levels, with three crRNAs (CRISPR RNAs) leading to ∼ 70–80% reduction, and five spacers resulting in an α-amylase gene knockdown of > 90% measured on both mRNA and protein activity levels. Our results indicate that this technology can be used to increase or modulate gene knockdown for efficient post-transcriptional gene silencing in hyperthermophilic archaea, and potentially also in other organisms.